Distribution and Abundance of Harpacticoid Copepods in Sandy Beaches; Namsai Beach in Chonburi Province, Prasae Beach in Rayong Province and Mook Kaew Beach in Trat Province : การแพร่กระจายและความชุกชุมของฮาร์แพคทิคอยโคพีพอด บริเวณหาดทราย; หาดน้ำใส จังหวัดชลบุรี, หาดประแสร์ จังหวัดระยอง และหาดมุกแก้ว จังหวัดตราด - Saowakul, Weerawan; Chullasorn, Supawadee; Kangtia, Pawana (Advanced Science Journal, 2023)
The objectives of this research was to study the distribution and abundance of harpacticoid copepods from three tourism sandy beaches; Namsai beach in Chonburi Province, Prasae beach in Rayong Province and Mook Kaew beach in Trat Province. Collected sediments samples 4 were collected from stations and 1 time in each beach during July - August 2020. The environmental factors, including temperature, salinity, pH and dissolved oxygen were measured. A total of 12 genera from 9 families was recorded ; genus Nitokra (family Ameiridae), genus Scottolana (family Canuellidae), genus Ectinosoma and genus Halectinosoma (family Ectinosomatidae), genus Harpacticus and genus Tigriopus (family Harpacticidae), genus Laophonte (family Laophontidae), genus Leptastacus (family Leptastacida), genus Longipedia (family Longipediidae), genus Shizopera and genus Paramphiascella (family Miraciidae) and genus Apodopsyllus (Family Paramesochridae). The total number of harpacticoid copepods were found from all sandy beaches are 11,133 individuals. In Namsai beach were found 9 genus, 809 ind./10 cm2, Prasae beach were found 8 genus, 932 ind./10 cm2, Muk Kaew beach were found 5 genus, 9,392 ind./10 cm2 and was found that harpacticopods in Mook Kaew beach in Trat province has the highest numbers. Harpacticoid copepod showed highest abundance at Muk Kaew beach (5 genus, 9,392 ind./10 cm2), followed by Prasae beach (8 genus, 932 ind./10 cm2) and Namsai beach (9 genus, 809 ind./10 cm2). Indicates that the sandy beach is a popular tourist destination, the harpacticoid copods are easily disturbed and therefore of number decreases.